Relation of seminal plasma hormonal levels with quality of frozen semen in cattle
Levels of seminal plasma Testosterone, Tri-iodo-thyronine T3) and Thyroxin T4) in the fresh ejaculatet were estimated aild its correlation with post thaw seminal quality was found out. The levels of these honnones were significantly_ p<0.01) higher in HF semen than in crossbred and Murrah semen. These hormones w re positively correlated with sperm motility, volume, total sperm concentration and percent live·sperm. A significant positive correlation with sperm penetration distance (SPD), perc nt sperm responding to hypo-osmotic swelling test (HOS) in fresh -and post-thawed semen with these hormones was also recorded. A positive correlation of SPD and HOS positive sperm with testosterone, T3 and T4; both in fresh and post-thawed semen proves their important role in maintaining initial quality of semen, indicating estimation of these hormones as a valuable tool fo _initial selection of bulls and _also for the selection of ejaculates for freezing. , number=1, journal=The Indian Journal of Animal Reproduction, author=KUMAR, SATISH and SRIVASTAVA, SUSHANT, year=2023, month=Feb., pages=68–73